YORUBA CULTURE INFLUENCE INTO CONTEMPORARY STAGE THROUGH WOLE SOYINKA’S THE SWAMP DWELLERS - Muhammad Baihaqi; Muhammad Yakob (UIN Alauddin Makassar, 2019)
This paper aims to observe the full development of literature on the African continent through special attention to a world-leading literary scholar from Africa, Wole Soyinka with his masterpiece drama the Swanp Dwellers. This paper also explore the history of the greatness of Wole Soyinka who continually nurtured Yoruba cultural traditions through her works. More interestingly, the description of Yoruba culture is not only seen in his works, but also has colored the life of the author himself. Although his mind and personality were influenced by the outside world when he continued his studies in the United Kingdom, his love and love for local cultural traditions, especially Yoruba culture, remained something to be prioritized. The method used is descriptive qualitative by using content analysis approach . The result of the research shown that the Yoruba culture with contemporary stage reflected into swamp dweller drama and had been influenced others cultural over the whole of Africa till now.Keywords: Yoruba, Wole Soyinka, Swamp Dwellers Abstrak Tulisan ini bertujuan untuk mengamati secara utuh perkembangan sastra di benua Afrika melalui perhatian khusus kepada seorang sarjana sastra terkemuka dunia yang berasal dari Afrika yaitu Wole Soyinka dengan drama terkenalnya the Swamp Dwellers. Tulisan ini juga akan menelusuri sejarah kehebatan Wole Soyinka yang secara terus menerus menyuburkan tradisi budaya Yoruba melalui karya-karyanya. Lebih menarik lagi penjabaran budaya Yoruba tidak hanya terlihat pada karya-karyanya, namun juga telah mewarnai kehidupan pengarang itu sendiri . Walaupun pikiran dan pribadinya telah dipengaruhi oleh dunia luar sewaktu beliau melanjutkan studinya di United Kingdom, namun cinta dan rasa kasihnya kepada tradisi budaya setempat terutama budaya Yoruba tetap menjadi sesuatu yang harus diutamakan. Metode yang digunakan dalam penelitian ini adalah deskriptif kualitatif melalui pendekatan content analisis. Hasil penelitian memperlihatkan bahwa budaya Yoruba dengan latar kontemporer tergambarkan melalui drama swamp dweller yang ditulis oleh Wole Soyinka dan juga telah mempengaruhi budaya lainnya di afrika hingga saat ini.. Kata kunci: Yoruba , Wole Soyinka, Swamp Dweller